The Effect of Dobutamine Administration on Oxygen Saturation in Infant's Persistent Pulmonary Hypertension of The Newborn (PPHN) - Itaqullah, Yusfa Iswinda; Airlangga, Muhammad Perdana; Triastuti, Nenny; Djalilah, Gina Noor; Anas, Muhammad (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: PPHN of infants are severe cases because the rate of disability and death in infants is relatively high, reaching around 10-20% of cases. Therefore, prompt, accurate, and rational management is needed to reduce cases number of records and deaths. The incidence of PPHN is 2-6 out of 1000 live births; in Surabaya, the incidence was 42 babies per 1000 live births from April to September 2017. Dobutamine is an effective therapy that can support good morbidity and mortality. Therefore, therapeutic options in infants with PPHN in the form of dobutamine are often used.Objective: To determine the effect of dobutamine administration on oxygen saturation in infants with persistent pulmonary hypertension of the newborn (PPHN)Method: A cross-sectional design with a consecutive sampling of 50 infants with PPHN who received dobutamine therapy at the Hospital of Siti Khodijah Muhammadiyah Sepanjang. Data collection using medical records. Results: The average increase in oxygen saturation before and after being given dobutamine was 36.0%. No difference in the increase in oxygen saturation based on the duration of dobutamine administration. The dobutamine dose's effect on the oxygen saturation increase in infants with PPHN.Conclusion: The results of this study indicate a significant effect of dobutamine administration on increasing oxygen saturation in PPHN infants.